Normative Critique of Passive Money Laundering Formulation in Indonesian Criminal Law: An Islamic Proportionality Perspective - Aditya Wiguna Sanjaya; Kiki Kristanto; Nabilaa Mohamed; Taufik Firmanto; Rudhi Achsoni (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
Money laundering crimes are generally classified into active and passive forms. In the Indonesian context, passive money laundering based on Article 607 paragraph (1) letter (c) of the Criminal Code adopts the pro parte dolus pro parte culpa model which equates criminal liability between intentional acts and those committed due to negligence. This approach raises normative issues related to the principle of proportionality which requires differentiating sanctions based on the degree of error. This study aims to analyze the principle of proportionality in Islamic criminal law and evaluate the suitability of the formulation through a comparative approach. This study uses normative legal methods with legislative, conceptual, and comparative approaches. The analysis was carried out on the provisions of Indonesian criminal law, Islamic criminal law principles, and several relevant foreign legal systems. The results of the study show that Islamic criminal law expressly distinguishes the level of error in the imposition of sanctions, as reflected in the concepts of qisas and diyat. This principle is also in line with a number of modern legal systems that separate intentional crimes (dolus) and negligent crimes (culpa) with different criminal consequences. On the other hand, the pro parte dolus pro parte culpa model in the Criminal Code has the potential to obscure these differences by imposing equivalent sanctions, thereby weakening the principle of proportionality and risking substantive injustice. This research contributes theoretically through strengthening the study of comparative criminal law based on the integration of Islamic law perspectives, as well as practically by recommending the reformulation of criminal policies to ensure more optimal proportionality and justice.